I'm having hard time figuring out the following question.

Suppose that for each k, there is a box containing k red marbles n-k green marbles. $(k=0,1,2,...,n)$ One box is chosen from these $n+1$ boxes, and then two marbles are selected at random without replacement from the chosen box. Find the probability that to marbles are red.

Initially I thought,

$$\binom{n+1}{1}\binom{n}{k}\binom{n-1}{k-1}$$ would be the number of ways to choose a box among $n+1$ boxes, and first and second red marble respectively. However, I got stuck, how do I even compute the sample space?

  • $\begingroup$ You don't really need to do any counting. The probability you are trying to compute is just $\sum_k P(E_k) P(R_1 \mid E_k) P(R_2 \mid E_k \cap R_1)$, where $E_k$ is the event that the $k$-th box is chosen, $R_1$ is the event that the first marble selected is red, and $R_2$ is the event that the second marble is red. $\endgroup$ – Ben CW Oct 10 '16 at 3:08

Let $X$ be the box you sampled and $Y$ is the # of red marbles if you sample two marbles from $X$. Then $$ \Pr(Y = 0 | X = k) = \frac{{n-k \choose 2}}{n \choose 2} = \frac{(n-k)(n-k-1)}{n(n-1)} $$ Therefore, \begin{align} \Pr(Y = 0) &= \sum_{k=0}^n \Pr(Y = 0 |X = k)\Pr(X = k) \\ &= \sum_{k=0}^n \frac{(n-k)(n-k-1)}{n(n-1)}\cdot \frac{1}{n+1} \\ &= \frac{1}{(n+1)n(n-1)}\cdot \sum_{k=0}^n (n-k)(n-k-1) \\ &= \frac{1}{(n+1)n(n-1)}\cdot \sum_{k=0}^n k(k-1) \end{align} Use $\sum_{k=0}^n k^2 = \frac{n(n+1)(2n+1)}{6}$ and $\sum_{k=0}^n k = \frac{n(n+1)}{2}$ to simplify the formula above.


The probability that two marbles drawn from the same box selected without bias are both red will be given by the Law of Total Probability. Where $X$ is the count of red marbles drawn, and $K$ is the count of red marbles in the box selected, that is:

$$\begin{align}\mathsf P(X=2) ~=~& \sum_{k=1}^n \mathsf P(K=k)\mathsf P(X=2\mid K=k) \\[2ex]~=~& \frac 1{n+1}\sum_{k=2}^n \binom{k}{2}\Big/\binom{n}{2}\\[1ex]~\vdots~&\\[1ex] ~=~& \bbox[silver ,1pt]{\color{silver}{\frac 13}}\end{align}$$

And similarly for $\mathsf P(X=1), \mathsf P(X=0)$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.